Experimental and numerical study on the soil arching effect caused by deep-buried shield tunneling - Xu Song; Chang-Wei Miao; Ren-Peng Chen; Xiao-Ning Deng; Yu Zhang; Jun-Qing Wang; Xiao-Fei Chen (Underground Space)
The soil arching effect induced by deep-buried shield tunneling strongly influenced the ground stress and displacement. Therefore, revealing the evolution mechanism of the soil arching effect is a prerequisite for accurately predicting the tunnel load, which has not been understood in deep-buried conditions. Three model tests and eight numerical simulations were carried out to enhance the understanding of the soil arching evolution, in which the stress field, displacement field, and strain field were analysed. The experimental and numerical results indicated that the ground reaction curve presented a two-stage development process of an initially linear decrease followed by a gradual decrease. Compared with the theoretical tunnel loads, the measured and numerical values are relatively larger due to the loosening earth pressure theory ignoring the evolution process of the soil arching effect. The soil arching height decreases with the increase in stress level, measuring 1.75D (the initial diameter of the model tunnel), 1.65D, and 1.61D, respectively, which results from the lagging evolution of the soil arching effect under high-stress conditions. The formation of the shear band was affected by the stress-dependent dilatancy of the soil. At low stress levels, the shear band develops vertically upward. In contrast, at higher stress levels, the shear bands tilt towards the lateral side.